Complex Ownership Structures and Corporate Valuations - Laeven, Luc; Levine, Ross (Review of Financial Studies, 2008)
[The bulk of corporate governance theory examines the agency problems that arise from two extreme ownership structures: 100% small shareholders or one large, controlling owner combined with small shareholders. In this paper, we question the empirical validity of this dichotomy. In fact, one-third of publicly listed firms in Europe have multiple large owners, and the market value of firms with multiple blockholders differs from firms with a single large owner and from widely held firms. Moreover, the relationship between corporate valuations and the distribution of cash-flow rights across multiple large owners is consistent with the predictions of recent theoretical models.]